미래교육과 교육공간의 혁신에 관한 연구 - 임미숙(Mi Suk Lim) (디지털콘텐츠학회논문지, 2022)
사람들은 메타버스라는 가상공간을 만들고 그 안에 아바타를 두어 서로 소통을 하고자 한다. 가상이든 현실이든 사람들이 커뮤니케이션할 수 있는 공간을 만드는 것이 사람에게는 절대적으로 필요하다. 코로나 발생 이후 비대면 온라인 교육이 활성화되면서 교수자들은 기존의 교실에서의 일방적인 수업방식에서 다양한 프로그램을 활용하여 학생들이 참여할 수 있도록 교육방식을 개선하였다. 그 과정에서 교육 공간의 변화를 인식하고 학생들과 교수자가 함께 다양한 교육 공간을 요구하게 되었다. 스마트한 교육환경이 요구되면서 이제는 컴퓨터와 모니터가 없는 강의실은 답답하게 느껴질 정도이다. 본 연구는 이러한 변화에 대한 요구로 교육 공간의 변화를 인식하고 미래교육의 일환으로 교육공간을 학습자의 관점에서 교육공간을 다양하게 변화시킬수있도록 시뮬레이션하여 구현해 보았다. 이를 통해 교육 공간의 효율적인 활용으로 학교에서 교사와 학생, 학생과 학생 간의 소통이 확대되길 바란다. 본 연구를 통해 스마트한 교육 공간의 변화가 학생에게 만족과 편리함을 제공하여 디지털전환시대의 미래사회를 만드는 데 많은 영향을 주리라 기대한다. People want to communicate with each other by creating a virtual space called a metaverse and placing an avatar in there. Whether it is virtual or real, it is absolutely necessary for humans to create a space where people can communicate. As non-face-to-face online education has been activated since the outbreak of COVID-19, professors have improved their educational methods so that students can participate by using various programs other than one-sided teaching methods in existing classrooms. In this process, students and professors recognized changes in educational space and required various educational spaces together. As a smart educational environment is required, classrooms without computers and monitors now feel stuffy. This study simulated and implemented the educational space to recognize the change in the educational space as a demand for these changes and to change the educational space in various ways from the perspective of learners as part of future education. It is expected that communication between professors and students in school classrooms will be expanded through such efficient use of educational space. Through this study, it is expected that the change in smart educational space will have a great influence on creating a future society in the digital transformation era by providing satisfaction and convenience to students. KCI Citation Count: 4